Using a longitudinal multi-method approach to document, assess, and understand adaptations in the Veterans Health Administration Advanced Care Coordination program - McCreight, Marina; Rohs, Carly; Lee, Marcie; Sjoberg, Heidi; Ayele, Roman; Battaglia, Catherine; Glasgow, Russell E.; Rabin, Borsika Adrienn (Frontiers in Health Services, 2022)
Background: Understanding adaptations can support iterative refinement of the implementation process, advance implementation science frameworks, and inform future scale out of programs. Systematic documentation of adaptations across the life course of programs is not routinely done, and how one can efficiently capture adaptations in complex, real world studies is still not well understood. Methods: We used a multi-method longitudinal approach to systematically collect information about adaptations during pre-implementation, implementation, and sustainment for the Veteran Health Administration (VA) Advanced Care Coordination program. This approach included documenting adaptations through a real-time tracking matrix, process maps, team meeting minutes, and adaptation interviews. Data collection was guided by the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) enhanced framework for reporting adaptations and modifications to evidence-based interventions (FRAME) model. Results: A total of 144 individual adaptations were identified across two implementation sites and the four data sources; team consensus and member-checking processes resulted in 50 unique adaptations. Most adaptations took place during the early implementation and mid-implementation phases. Most adaptations were: 1) planned; 2) made to address changes in program delivery element; 3) made to extend a component; 4) related to the core component of the intervention concerning notification of the community emergency department visit; 5) initiated by the entire or most of the team; 6) made on the basis of: pragmatic/practical considerations; 7) made with an intent to improve implementation domain (to make the intervention delivered more consistently; to better fit the local practice, patient flow or Electronic Health Record (EHR) and/or for practical reasons); 8) a result of internal influences; 9) perceived to impact the RE-AIM implementation dimension (consistent delivery of quality care or costs). Team meeting minutes and process maps captured the highest numbers of unique adaptations (n=19 and n=13 respectively). Conclusion: Our longitudinal, multimethod approach proved a feasible way to collect adaptations data. This approach allowed engagement of multiple team members, resulting in richer consensus discussions and providing a broader understanding of adaptations that took place. Recommendations of future research include pragmatic assessment of the impact of adaptations and meaningful data collection without overburdening the implementation teams and front-line staff.